2021
DOI: 10.1007/s40789-021-00431-7
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of methane adsorption in diverse organic pores in shale reservoirs with multi-period geological evolution

Abstract: In shale reservoirs, the organic pores with various structures formed during the thermal evolution of organic matter are the main storage site for adsorbed methane. However, in the process of thermal evolution, the adsorption characteristics of methane in multi type and multi-scale organic matter pores have not been sufficiently studied. In this study, the molecular simulation method was used to study the adsorption characteristics of methane based on the geological conditions of Longmaxi Formation shale reser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The coal and gas outburst dynamics are the result of the combined effects of ground stress, gas pressure, and coal mechanical properties [1][2][3][4][5][6]; it always threatens the safety of underground production as a serious mine disaster [7][8][9][10][11][12]. In some soft outburst coal seams with low permeability in China, the coal seam has suffered from strong structural compression deformation due to the influence of multistage geological structure, and its primary structure has been damaged seriously, and the coal body strength and coal seam permeability are low [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The coal and gas outburst dynamics are the result of the combined effects of ground stress, gas pressure, and coal mechanical properties [1][2][3][4][5][6]; it always threatens the safety of underground production as a serious mine disaster [7][8][9][10][11][12]. In some soft outburst coal seams with low permeability in China, the coal seam has suffered from strong structural compression deformation due to the influence of multistage geological structure, and its primary structure has been damaged seriously, and the coal body strength and coal seam permeability are low [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many experiments on the permeability of coal rocks under thermal action have found some special phenomena and laws [15][16][17][18]. In the experiments on the permeability of lignite under the e ect of temperature and triaxial stress, Hu et al [19] found that the permeability of coal samples showed a monotonic decreasing pattern in the range of room temperature to 300 °C with the increase of temperature, although the axial pressure and the surrounding pressure applied to the coal samples always kept constant pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Pore systems in shale are important for gas storage and transport [3][4][5][6]. From the start of shale gas development and production, pore structure has been one of the key research topics [7,8], and numerous studies have been carried out on pore systems in shale [9,10]. These have shown that shale contains organic pores and inorganic pores, e.g., within clays or formed by carbonate dissolution [11,12].…”
Section: Introductionmentioning
confidence: 99%